Distal Femoral Physeal Fractures - Young, Ernest Y.; Stans, Anthony A. (The Journal of Knee Surgery, 2018)
Physeal fractures of the distal femoral are rare injuries accounting for less than 2% of all physeal injuries, and tend to have a worse prognosis than similar injuries in other locations. This article reviews the evaluation (including imaging), classification, and treatment of these injuries, and discusses their most important complications and their management, including vascular injury and growth arrest.
Keywords: pediatric orthopaedics; distal femur fracture; physeal fracture; growth arrest